Where the wind leads : a refugee family's miraculous story of loss, rescue, and redemption - Chung, Vinh, 1975- (W Publishing, an imprint of Thomas Nelson, 2014)
A family's journey from pre-war Vietnam, through pirate attacks in the open sea, to a new home in Fort Smith, Arkansas, where poverty and discrimination could not prevent the author from graduating from Harvard Medical School.